(untitled) (Web of Teachers: Inderscience Research, 2023)
English for Specific Purposes (ESP) is a specialized branch of English language teaching that focuses on equipping learners with the language skills and knowledge required for their particular fields of study or professions. This paper explores the pivotal role of the teacher in the ESP classroom, shedding light on the multifaceted responsibilities and strategies required for effective ESP instruction. Drawing on an extensive review of relevant literature and practical insights, the paper delves into the teacher’s role as a facilitator, needs analyst, materials developer, motivator, and cultural mediator in ESP contexts. It highlights the teacher’s vital function in tailoring instruction to meet learners’ specific linguistic and professional needs, as well as fostering motivation and engagement within the classroom. Furthermore, the paper addresses the challenges and opportunities presented to ESP teachers in the digital age, where technology plays an increasingly significant role in language learning. This analysis not only contributes to a deeper understanding of the teacher’s role in ESP education but also provides valuable guidance for educators, curriculum developers, and educational policymakers seeking to enhance the quality and relevance of ESP instruction in diverse professional contexts.